Simultaneous second and third harmonics generation in periodically poled lithium niobate: Coupling and competition - Liu, Junming; Liu, Liqiang; Hong, Lihong; Li, Zhiyuan (Chinese physics B, 2025)
Conventional approaches for obtaining the second and third harmonics typically employ several nonlinear crystals to generate them, which is restricted in application due to the complexity of the optical path and the bulkiness of the device. In this work, we present a comprehensive theoretical and numerical investigation of the simultaneous generation and competition between the second harmonic waves (SHW) and the third harmonic waves (THW) in a single nonlinear crystal. Through analyzing both small-signal and large-signal regimes, we reveal the complex coupling mechanisms between SHW and THW generation processes. Using periodically poled lithium niobate as an example, we demonstrate that the relative conversion efficiencies between SHW and THW can be freely adjusted by controlling the input fundamental wave power. This work provides new insights for designing efficient frequency converters capable of generating both SHW and THW outputs with controllable intensity ratios.